Motor speech patterns in Huntington disease. (26th November 2019) - Diehl, Sarah K.; S. Mefferd, Antje; Lin, Ya-Chen; Sellers, Jessie; E. McDonell, Katherine; de Riesthal, Michael; Claassen, Daniel O.
Abstract : Objective: Dysarthric speech of persons with Huntington disease (HD) is typically described as hyperkinetic; however, studies suggest that dysarthria can vary and resemble patterns in other neurologic conditions. To test the hypothesis that distinct motor speech subgroups can be identified within a larger cohort of patients with HD, we performed a cluster analysis on speech perceptual characteristics of patient audio recordings. Methods: Audio recordings of 48 patients with mild to moderate dysarthria due to HD were presented to 6 trained raters. Raters provided scores for various speech features (e.g., voice, articulation, prosody) of audio recordings using the classic Mayo Clinic dysarthria rating scale. Scores were submitted to an unsupervised k-means cluster analysis to determine the most salient speech features of subgroups based on motor speech patterns. Results: Four unique subgroups emerged from the cohort of patients with HD. Subgroup 1 was characterized by an abnormally fast speaking rate among other unique speech features, whereas subgroups 2 and 3 were defined by an abnormally slow speaking rate. Salient speech features for subgroup 2 overlapped with subgroup 3; however, the severity of dysarthria differed. Subgroup 4 was characterized by mild deviations of speech features with typical speech rate. Length of CAG repeats, Unified Huntington's Disease Rating Scale total motor score, and percent intelligibility were significantly different for pairwise comparisons of subgroups. Conclusion: This study supports the existence of distinct presentations of dysarthria in patients with HD, which may be due to divergent pathologic processes. The findings are discussed in relation to previous literature and clinical implications.